PENYULUHAN KEPARIWISATAAN DI LPK MAPINDO BADUNG BALI - I Made Bayu Wisnawa (Synergy and Society Service, 2023)
With the theme of tourism education, this community service aims to prepare human resources for tourism. The focus of its activities is increasing and applying tourism knowledge in the new normal era. The method is lecture and discussion. The study materials provided include (i) Tourism, (ii) History of Bali Tourism, (iii) Impact of Tourism, (iv) Changes in the Tourism Industry, (v) Mass Tourism, vi) Hospitality Industry, vii) CHSE, (viii) Sustainable Tourism, (ix) ) Tri Hita Karana and (x) Government Policy. Success was measured using a paired t-test. Pretest and post- test questionnaires were used as instruments. The activity results showed that the participants' knowledge increased by 5.7 points with a t-test sample t-test of 0.000. Keywords: Covid-19, Tourism, New normal, Sustainable tourism.